Current successes and remaining challenges in protein function prediction - Jeffery, Constance J. (Frontiers in Bioinformatics, 2023)
In recent years improvements in protein function prediction methods have enabled increasing success in annotating protein sequences. Yet for many sequenced genomes the functions of over 30% of the protein coding genes remain unknown. Protein functions vary widely from catalyzing chemical reactions, to binding DNA or RNA, or forming structures in the cell, and some types of functions are challenging to predict due to the physical features associated with those functions. Other complications in understanding protein functions are due to many proteins having more than one function or very small differences in sequence or structure that correspond to different functions. We will discuss some of the recent developments for predicting protein functions and some of the remaining challenges.